Observation of Clinical Profile of Different Types of Meningitis in a Tertiary Care Hospital - Dr. Md. Atiqul Islam, (SSB Global Journal of Medical Science, 2023)
Background: Meningitis, an inflammation of the membranes surrounding the brain and spinal cord, presents significant diagnostic challenges due to its varied etiologies and overlapping clinical symptoms. This study aims to observe and document the clinical and laboratory characteristics of viral, bacterial, and tubercular meningitis in a tertiary care hospital setting. Methods: This descriptive observational study was conducted at the Department of Neuromedicine, Cumilla Medical College Hospital, Bangladesh, from January 2020 to December 2020. We enrolled 159 patients diagnosed with meningitis based on clinical, biochemical, and investigative criteria. Detailed demographic data, clinical examination findings, and relevant investigations, including cerebrospinal fluid (CSF) studies, were recorded. Data analysis was performed using SPSS software version 20 and MS-Excel 2016. Results: Among the 159 participants, 36.7% were diagnosed with bacterial meningitis, 32.5% with viral meningitis, and 24.9% with tubercular meningitis. Fever was a universal symptom, while headache was reported by 87.3% of viral, 87.1% of bacterial, and 95.2% of tubercular meningitis patients. Vomiting was more prevalent in tubercular (57.1%) and bacterial (50%) meningitis. Laboratory findings showed the highest mean white blood cell count in bacterial meningitis (11803.18±2905.55 cells/cmm). C-reactive protein levels were also highest in bacterial meningitis (21.23±16.20 mg/dl). Elevated adenosine deaminase levels were a distinguishing feature of tubercular meningitis (14.18±10.60 Unit/L). Conclusion: This study highlights the distinct clinical and laboratory profiles associated with different types of meningitis. The findings emphasize the importance of comprehensive evaluations for accurate diagnosis and effective management of meningitis. Further research should aim to refine diagnostic criteria and explore advanced diagnostic tools to improve patient outcomes.